The Nonmydriatic Fundus Camera in Diabetic Retinopathy Screening: A Cost-Effective Study with Evaluation for Future Large-Scale Application. (3rd November 2016) - Scarpa, Giuseppe; Urban, Francesca; Vujosevic, Stela; Tessarin, Michele; Gallo, Giovanni; Visentin, Annalisa; Foglia, Emanuela; Ferrario, Lucrezia; Midena, Edoardo
Abstract : Aims . The study aimed to present the experience of a screening programme for early detection of diabetic retinopathy (DR) using a nonmydriatic fundus camera, evaluating the feasibility in terms of validity, resources absorption, and future advantages of a potential application, in an Italian local health authority. Methods . Diabetic patients living in the town of Ponzano, Veneto Region (Northern Italy), were invited to be enrolled in the screening programme. The "no prevention strategy" with the inclusion of the estimation of blindness related costs was compared with screening costs in order to evaluate a future extensive and feasible implementation of the procedure, through a budget impact approach. Results . Out of 498 diabetic patients eligible, 80% was enrolled in the screening programme. 115 patients (34%) were referred to an ophthalmologist and 9 cases required prompt treatment for either proliferative DR or macular edema. Based on the pilot data, it emerged that an extensive use of the investigated screening programme, within the Greater Treviso area, could prevent 6 cases of blindness every year, resulting in a saving of€ 271, 543.32 (−13.71%). Conclusions . Fundus images obtained with a nonmydriatic fundus camera could be considered an effective, cost-sparing, and feasible screening tool for the early detection of DR, preventing blindness as a result of diabetes.